Guiding the use of collective feedback displayed on heatmaps to reduce group conformity and improve learning in Peer Instruction. (19th June 2020) - Michinov, Nicolas; Anquetil, Éric; Michinov, Estelle
Abstract: Peer Instruction is an active learning method widely used in higher education, whereby students answer a series of questions twice, once before and once after peer discussion. There is an ongoing debate as to whether a collective feedback should be given after the students' initial answer, and if so, how the frequently observed group conformity can be avoided. This study examined whether guiding on the use of this feedback can reduce group conformity and improve learning using an interactive learning environment to administer a new type of quiz using graphics, and delivering collective feedback to the whole class in a novel heatmap format. In the experimental group, the teacher told the students that the answer indicated by the heatmap was not necessarily the correct one; this information was not given to students in the control group. Results revealed that guided students were less likely to adopt the (incorrect) majority answer than the non‐guided students, and consequently, they were more likely to improve their learning by reaching an agreement about the correct answer through discussion with their peers. These findings suggest that guiding students in their use of collective feedback may have a crucial role in Peer Instruction. Lay Description: What is currently known about the subject matter: Peer Instruction is an interactive learning method engaging students in peer discussion. In Peer Instruction, students answer a series of questions twice, once before and once after peer discussion. Multiple‐choice questions are used to give collective feedback displayed in bar‐chart format to the whole class. After collective feedback of the first answer to a question, students tend to give the most common answer when answering the second time. What this paper adds: The questions were in a graphic format (instead of multiple‐choice questions) and students answered on tablets with a stylus. Collective feedback was given in a heatmap format (instead of bar charts) to the whole class. The Peer Instruction method is enhanced when the teacher gives advice about the use of collective feedback. Guiding helps students to use the collective feedback efficiently, and leads them to discuss their answers with a peer instead of conforming to the (incorrect) majority answer. The implications of study findings for practitioners: Teachers are often encouraged to promote active learning in their class. In Peer Instruction, they can administer questions and give collective feedback to engage peer discussion to improve learning. It is crucial that teachers give students advice to prevent them adopting the most common answer following collective feedback. Guiding students reduces group conformity and increases learning gains because students do not systematically adopt the most common answer.